Physical and mechanical properties of iron powder filled polystyrene composites - TAŞDEMİR, MÜNİR (TAYLOR & FRANCIS INC, 2006)
This article reports on an experimental study of the physical and mechanical properties of Polystyrene (PS) and Fe-PS polymer composites containing 5, 10, and 15 vol.% of Fe powder. After mixing Fe powder and PS in a twin-screw extruder, an injection-molding machine was used to prepare unfilled PS and Fe-PS polymer composite samples. After that, the material properties were experimentally determined for each sample. The investigated material properties included the modulus of elasticity, yield and tensile strength, % elongation, Izod impact strength (notched), hardness (Shore D), melt flow index (MFI), heat deflection temperature (HDT), Vicat softening point, and glass transition temperature (T-g). The results indicated that, compared to the unfilled PS, an addition of Fe into PS decreases the yield and tensile strength, % elongation, and Izod impact strength. Furthermore, it was determined that the Fe particles increase the modulus of elasticity, hardness, MFI, Vicat softening point, and HDT values.
Keywords: Fe powder; polymer composite; polystyrene; DENSITY POLYETHYLENE COMPOSITES; METAL POWDERS; CONDUCTIVITY